Rubric for Measuring Psychomotor and Affective Learning Domain. - Nathan, Shelena Soosay; Berahim, Mazniha; Ramie, Rosni (Pertanika Journal of Social Sciences & Humanities)
Designing a reliable measurement of the psychomotor and affective learning domains is a major challenge. One assessment tool, the rubric, provides flexibility in assessing and improves grading consistencies. But students are not being assessed properly as only one rubric is used to evaluate different categories of a project, causing inconsistencies in grading. Thus, an assessment rubric for different categories of a project was created, incorporating the psychomotor and affective learning domains aligned with Bloom's Taxonomy. To validate the rubrics, intra-class coefficient (ICC) and reliability tests were done using the Statistical Package for the Social Sciences (SPSS) tool. Analysis was done to determine grading consistency and agreement level among two randomly chosen evaluators when using the rubrics and to evaluate whether clearly defined assessment metrics were used in grading projects. The results showed that the psychomotor rubric has strong inter-rater reliability with scores of 0.90 and 0.86; this suggests that variables in the rubric were 'very good' at measuring the end product. However, the affective rubric shows slightly weak reliability. This might be due to the different way evaluators assess the same work as some tend to be lenient, while others are strict. The developed rubrics enables evaluators to better assess students so that students obtain justified grades according to the quality of their project.